Modernizing your IT infrastructure with IBM b-type Gen 6 Storage Networking and IBM Spectrum storage products - Bosisio, Simone (IBM redbooks., 2018)
Abstract This IBM® Redbooks® publication describes the challenge that most data centers face when updating and modernizing their IT infrastructure. New business demands are driving new applications, joining, and creating in the digital world. A rich, meaningful digital experience is the key to effective engagement in today's integrated digital world. Companies are able to customize digital experiences for their employees with personalized, targeted content for fully connecting with customers, co-workers, and business partners in the most powerful and productive ways. To achieve this, a robust infrastructure is required. Speed of access to data is one of the most important factors. The development of the flash storage devices helped with the insatiable desire for data access speed, but even that is not enough for the most demanding uses. The needs of SAN switches, servers, and software defined infrastructure (SDI) technologies are all requiring more; therefore, the bigger picture needs to be wholly analyzed to build a balanced ecosystem. This publication can help you with planning for growth in your IT infrastructure. This publication explores the concept of modernization and considers important aspects of IT, such as SAN switches, storage systems, and software defined storage.